Klaus Mann and the Weimar Republic: literary tradition and experimentation in his prose, 1924-1933 - Ford, Alison (1999)
This study developed from an initial interest in the literature of the German exiles in which canon Klaus Mann's work between 1933 and 1945 figured prominently. This in turn evoked a curiosity toward this still relatively unknown son of Thomas Mann, intensified not least by the pathos of a life characterised by early promise, fame and prominence that ended in obscurity, despair and suicide. Yet these aspects of Klaus Mann's life appeared to have been overlooked by British scholars and with them the early and later years of Mann's career.